CRDTs for non-synchronised networked applications. (Research'eu results magazine)
Historically, the only way to prevent two computers using the same online application from modifying the same data at the same time has been synchronisation. Claiming that this system is inefficient and a waste of resources, the SYNCFREE project suggests a better approach, using 'Conflict-free replicated data types' (CRDTs).